THREE-DIMENSIONAL MULTIPHASE MODEL OF HYDRODYNAMICS IN AN OXIDATION DITCH REACTOR - HADISOEBROTO (NIM : 35311301), ROSITAYANTI
In a wastewater treatment reactor, hydrodynamics—as the study of fluid flow patterns—plays a crucial role to assure that the process runs effectively. Hydrodynamic characteristics that support the performance improvement are the reduction of dead zones as well as the dispersion and multiphase interactions (water-sludge, water-air, and air-sludge). It is quite hard to observe the multiphase interactions that a mathematical simulation model is needed to depict the interactions between phases. The hydraulic and physical aspects of a treatment unit will affect the process performance. Besides the risk of interfering with the ongoing process, the evaluation of an extensive treatment unit using a tracer study requires a considerable amount of time and financial resources. Thus, a mathematical model has been carried out to simulate the flow in the treatment unit. The mathematical model of hydrodynamics was constructed based on the governing equations of momentum and continuity equations, numerically solved in one-, two-, and three-dimensional basis. The numerical differentiation of the governing equations was carried out using finite volume method, assisted by the computation through the Ansys Fluent programming application. The developed model has been calibrated using velocity measurement data, compared to the simulation results. The validation was executed by secondary data, that is by running several simulations based on the research outcome and comparing the results. The simulations were conducted for one-, two-, and three-phase flow within various geometrical configurations. It can be seen from the comparison results of one-, two-, and three-phase simulation of a rectangular reactor that the three-phase simulation is capable of illustrating the interactions between the fluid (water), gas (air), as well as sludge as both solids and a mixture of wastewater. The appropriate model for the two-phase simulation is Volume of Fluid (Vof) and Eulerian schemes. As for the three-phase simulation with aerators, the Eulerian model was used. The multiphase flow model is considered better than the single-phase simulation for the oxidation ditch reactor due to the presence of surface water phenomena which directly interact with the open air. The three-phase flow model representatively depicts hydrodynamic phenomena to the actual condition. The effective volume yielded by the three-phase flow model of 41.33% is lower than that of the two-phase simulation of 60.83%. It is induced by the presence of sludge as the solid phase that reduces the water volume, also by the friction between the water and the sludge surface which decreases the flow velocity. Based on the analysis of the effective volume, it can be seen that a “static” zone with a flow velocity below 10-5 m/s (nearly zero) emerged in the reactor without any additional diffuser or aerator. The tracer test delivered the amount of the effective volume of 32.94%, implying that only one-third of the designed volume is used for channeling the water. In the ancillary aerator simulation, the effective volume was boosted to 55.5%, though it had not been distributed evenly throughout the areas of inlet and outlet direction. The effective volume of the area alongside outlet direction was obtained of only 38%, while that of the inlet direction reached 73%. Hence, the average effective volume of the whole reactor was 55.5%; merely half of the designed volume was used for channeling the water. In general, the KLa value of aerators (0.0051) is higher than that of diffusers (0.0028–0.0031). Unaerated zones, nevertheless, hold a value of KLa that insignificantly differs with aerated zones. Therefore, the hydrodynamic simulation of oxidation ditches has to be approximated by the compressible flow model. The multiphase model performed on the oxidation ditch introduces a new approach namely three-phase interactions, with the presence of sludge in the form of solid-liquid media as sediments on the bottom of the reactor, discretely combined with the inlet wastewater flow. Partitioning the reactor into smaller subdomains was used as the grid generation technique to avoid inaccurate renderings of fluid flow that often occur on account of the erroneous meshing. Multiple Reference Frame (MRF) was applied particularly to the aerator subdomain and its surroundings to provide a positive pressure abiding the rotation direction. The vertical rotation of the aerator enhances the flow distribution along the aerators better than the diffusers type. The DO level in the reactor tends to increase as well and is more stable when aerators are used instead of diffusers, proven by the preferable KLa obtained for the aerator application. Hence, the presence of aerators is not only for supplying oxygen but also for balancing the flow distribution by keeping the sufficient flow velocity to steer clear of dead zones. This function has been attested by the lower percentage of dead zones of 27% at the inlet, compared with that of 62% at the outlet. The high proportion of dead zones at the outlet was caused by the occurrence of a short circuit flow pattern, drifting directly from the inlet to the outlet through the inlet bank of the reactor instead of circulating through the whole sections of the reactor.